Integration of Learning Theories to Build an Arabic Learning Ecosystem - Kafi, Fina Aunul; Nurhadi, Nurhadi; Ilma, Zidni (UAS PRESS, 2024)
In an effort to improve the effectiveness of Arabic language learning, a deep understanding of relevant learning theories and their application in a comprehensive learning ecosystem becomes fundamental. This study aims to establish the relationship between learning theories and the learning ecosystem implemented in Arabic classes at MAN 3 Jember. This research uses a qualitative approach with a case study type to collect data through in-depth interviews, observation, and document analysis. The results of this study show that the integration of cognitive, behavioris, and constructivis as learning theories into Arabic language learning in MAN 3 Jember can help create a conducive and comprehensive learning environment ecosystem in building students’ knowledge and understanding through social interaction, collaboration, and reflection in the context of Arabic language learning.